Classical and modern direction-of-arrival estimation - Tuncer, T. Engin; Friedlander, Benjamin (Academic Press, 2009)
This book is the definitive reference on both classical and modern techniques of direction-of-arrival (DOA) estimation, giving a concise and accessible introduction to their methods, together with an evaluation of their strengths and weaknesses. Written by the leading experts in the field, the connections between classical and modern techniques are fully drawn, while key applications are described in acoustic and sonic arrays and in sensor and ad-hoc networks. Suitable for the researcher and industry engineer, it will be a beneficial resource for using DOA techniques to develop applications.